Tracking violence: using structural-level characteristics in the analysis of domestic violence in chicago and the state of Illinois - Morgan, Rachel E. (Crime & delinquency, 2017)
Social disorganization theory proposes that specific neighborhood characteristics contribute to an increase in crime rates. In a disorganized community, informal social controls are not present; therefore, crime and delinquency flourish. Researchers have focused on these measures of social disorganization and the ability to explain public crimes. Recently, researchers have focused their attention to characteristics of socially disorganized areas and their ability to predict private crimes, such as domestic violence. This study contributes to the research on domestic violence and its applicability to social disorganization theory by examining domestic violence in Chicago neighborhoods and Illinois counties. Results indicate that different measures of social disorganization are significantly associated with domestic violence at different units of analysis.